Designing evidence and theory-based ICT tools for weight loss maintenance: the H2020 NoHoW toolkit - Marta M Marques; James Stubbs; Falko F Sniehotta; Marcela Matos; Graham Horgan; Ciaran Clissman; Mikka Ermes; Cassim Ladham; Berit L Heitmann (Frontiers Media S.A., 2015)
Background: Very few comprehensive treatments are currently available for weight loss maintenance (WLM). Research suggests that if interventions are to be effective in promoting sustained health behaviour change they should use theory- and evidence-based techniques. Information and Communication Technologies (ICT) have the potential for wide reach and low cost interventions, offering attractive tools for the implementation of effective behaviour change techniques. The NoHoW project is a European Union H2020-funded project bringing together leading experts in behaviour change, technology providers, and weight loss/ obesity to develop tools to help people maintain previously lost weight. Aim: NoHoW will carry out a large-scale European randomized controlled trial to test whether different evidence-based and novel behavior change, emotion- and self-regulation techniques delivered via an ICT Toolkit (TK), promote successful WLM. Method/Results: The TK includes a set of web-app tools and inputs from other technologies, such as smart scales and activity trackers, and offers a personalised behaviour modification feed-back system targeting weight, sleep, physical activity, and dietary behaviours. The TK is based on (1) evidence-based state-of-art theories of behaviour change, including techniques associated with self-regulation skills (Self-regulation Theory), building autonomous motivation (Self-Determination Theory), and emotional regulation, (2) web-design expertise, and (3) user-testing. Informed by the guidelines for the development of complex behavior change interventions and principles applied in previous theory-based behavior change interventions, we used a systematic approach to the translation of theory and evidence to ICT intervention components. This includes (1) developing theory-driven logic models of the TK, (2) identifying key theoretical constructs targeted, (3) selecting theory- and evidence-based techniques that are expected to impact on target constructs, and (4) translating these techniques into the TK principles and technical specifications.The technical specifications of the TK are currently being developed. Once the TK is finalized it will be pilot tested for one month after which users will rate their experience and perception of TK. The data will be used to refine the TK features and functionalities. After an initial pilot study of the entire ICT structure, a large-scale European 2 x 2 factorial (self regulation/motivation versus emotion-regulation) randomised controlled trial, will be conducted among overweight/obese adults that successfully lost ≥5% of their initial body weight in the last six months. Conclusion: This presentation will provide an overview of the process of development of the NoHoW TK focusing on the foundations, the TK content, and the results from a pilot user-testing and will be discussing the contribution of a systematic approach to the development of ICT solutions based on theory, evidence, and user-testing, to the advancement of the science of behavior change and implementation of sustainable solutions to WLM across Europe.